Enhancing Firm Value of Palestinian Public Listed Companies through Intellectual Capital Performance and Disclosure - Ammar, Ahmed Adel Mahmoud; Kamaruddin, Muhammad Iqmal Hisham (International Journal of Economics and Financial Issues, 2025)
Public listed companies in Palestine are enhancing their corporate governance practices, particularly following the introduction of the Code of Corporate Governance in 2009. This development presents an opportunity to boost firm value through various avenues, including intellectual capital. This paper explores the role of intellectual capital in increasing firm value within Palestinian public listed companies. Using a descriptive-analytical methodology, the study examines data from 12 years of annual reports (2011-2022) of listed corporations, employing STATA version 16 for analysis. The findings reveal that components of intellectual capital performance (HCE, SCE, CEE) and intellectual capital disclosure (HCD, SCD, CED) have direct influences on firm value. The research emphasizes the need for companies to focus on enhancing employee skills through effective training, leading to better resource utilization. This paper contributes to understanding how specific aspects of intellectual capital can serve as tools for management to assure stakeholders and enhance overall firm value.